Die Allgemeine Deutsche Bibliothek und die Allgemeine Literatur-Zeitung als Medien des literarischen Epochenwandels - Marcus Conrad (Recherches Germaniques)
In this contribution literary criticism between 1770 and 1810 is investigated by focusing on the Allgemeine Deutsche Bibliothek and the Allgemeine Literatur-Zeitung as leading reviewing organs. The context is characterized by the developments of the public sphere and a change in literary sensibilities, for the two periodicals were shaped by leading protagonists of the late Enlightenment with Nicolai as editor and publisher of the Allgemeine Deutsche Bibliothek on the one hand, and with representatives of Weimar Classicism and early Romanticism with Wieland, Goethe and August Wilhelm Schlegel as leading initiators of the Allgemeine Literatur-Zeitung on the other hand who can be seen as antagonists pursuing their own programmatic intentions. Those journals reflect the emergence of certain literary tendencies and played a decisive role in their propagation, at the same time as they were deeply involved in the functional mechanisms of the literary market, particularly since Nicolai and Bertuch as leading publishing booksellers participated directly in the establishment of both periodicals.